2006
DOI: 10.4049/jimmunol.177.9.5956
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T Cell-Induced, Bid-Dependent Apoptosis of Cutaneous Dendritic Cells Regulates T Cell Expansion and Immune Responses

Abstract: The fate of dendritic cells (DCs) after Ag presentation may be DC subset-specific and controlled by many factors. The role of activation-induced apoptosis in regulating DC function is not clear. We investigated the fate of cutaneous DCs (cDCs), specifically Langerhans cells (LCs), and observed that they undergo apoptosis after successful Ag presentation to CD4 T cells. Caspase-specific inhibitors revealed that LC lines use a type II apoptosis pathway in response to CD4 T cells. In support of this, BH3-interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 55 publications
3
14
0
Order By: Relevance
“…In other cell types, such as thymocytes or mature T-cells, ligation of death receptors leads to efficient cell killing solely through activation of caspase-8 and the downstream effector caspases (Ϫ3, Ϫ6, and Ϫ7) without the need for Bid-and mitochondrial pathway-mediated amplification of the caspase cascade. Therefore, islets are one of only a handful of primary cell types in which Fas-induced apoptosis is dependent on Bid (16,17,38). No pathology in the pancreas was seen when mice were injected with agonistic anti-Fas antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In other cell types, such as thymocytes or mature T-cells, ligation of death receptors leads to efficient cell killing solely through activation of caspase-8 and the downstream effector caspases (Ϫ3, Ϫ6, and Ϫ7) without the need for Bid-and mitochondrial pathway-mediated amplification of the caspase cascade. Therefore, islets are one of only a handful of primary cell types in which Fas-induced apoptosis is dependent on Bid (16,17,38). No pathology in the pancreas was seen when mice were injected with agonistic anti-Fas antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both direct and indirect effects of DCs on the establishment of an effective immune response are highly dependent on the viability of DCs (4,5). Numerous studies have implicated DC apoptosis in the persistence of infection and the promotion of carcinogenesis (5)(6)(7).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…Control mice had their ears tape-stripped 10× on both dorsal and ventral sides to activate LC migration. After 4 hours, mice were sacrificed and ears recovered and split into dorsal (UV exposed) and ventral (non exposed) sides to float in culture as described previously (30). After 3 days of culture, cells were counted in trypan blue to determine cell recoveries and viability, then adjusted to 4×105 cells/ml PBS.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we showed that Bid KO mice could promote enhanced contact hypersensitivity to hapten, and isolated LCs were resistant to apoptosis and able to induce enhanced immunity when transferred to naive recipients (30). Because LC function figures prominently in the mechanism of UV-induced immune suppression, we investigated whether Bid KO mice demonstrated altered responses to UV-induced damage by keratinocytes and LCs.…”
Section: Introductionmentioning
confidence: 99%